PERSEPSI MAHASISWA TERHADAP KOMPETENSI DOSEN DI FAKULTAS EKONOMI UNIVERSITAS GARUT - Lala Kemala Shafitri; Ramayani Yusuf (LPPM Universitas Dinamika Bangsa, 2023)
In this era of globalization, the world of education demands quality results. The quality of this output is strongly supported by the presence of teaching staff, because teaching staff is also a determining factor for the success of educational activities. This study aims to determine the influence of Student Perceptions on Lecturer Competence at the Faculty of Economics, University of Garut. The method used is quantitative method with a total sample of 95 respondents. The analysis technique uses simple correlation analysis and simple regression analysis with SPSS testing. The results of testing the hypothesis show that there is a positive influence on Student Perceptions of Lecturer Competence at the Faculty of Economics, University of Garut